Unstructured source artifacts ontology for requirement validation in GDSD - Altaf, Sohaib; Shah, Asadullah; Imtiaz, Najma; Shah, Abdul Salaam; Ahmed, Syed Faiz (Science Publishing Corporation, 2018)
Analyst while transforation, may not capture true representation of user opinion thus reating deviation fro actual user needs Roles of stakeholders is primary in both requirements elictation and alidation process In eliitation stage they are initators whereas in alidation stage they are authentiators of their needs Inaldi requireents if vverified may nit be deviation fro specified behavior but deiation fro user needs Requireents validation process ensure that requireents should be representating all priary and interediary artifacts as wellas shared opinions of their contribuors This highlights the importance of soure artifacts without whicch requireents alidation cannot assured Researhers didn't propose any framewoek for requireents alidation in ontt of GDSD in which source artifats grows exponentially and stakeholders are located in diversified loations Due to unstructured nature of source artifats they are not elecctronially indexed and versioned ccontrolled and this akes difficulty in presering them Requyirements validation is not possible when source artifacts are not available along with their contributors. This major contribution of this paper to address problem of requirements validation in GDSD in absence of stakeholders to make it collecting environment. This paper introduced ontological solution of requirement validation in which target artifacts are validated against source artifacts using their semantic relationship. This paper proposed as unstructured source artifact based ontological model for requirement validation in GDSD environment.